Carbohydrate–Lectin Interactions: An Unexpected Contribution to Affinity. (7th February 2017) - Navarra, Giulio; Zihlmann, Pascal; Jakob, Roman P.; Stangier, Katja; Preston, Roland C.; Rabbani, Said; Smiesko, Martin; Wagner, Bea; Maier, Timm; Ernst, Beat
Abstract: Uropathogenic E. coli exploit PapG‐II adhesin for infecting host cells of the kidney; the expression of PapG‐II at the tip of bacterial pili correlates with the onset of pyelonephritis in humans, a potentially life‐threatening condition. It was envisaged that blocking PapG‐II (and thus bacterial adhesion) would provide a viable therapeutic alternative to conventional antibiotic treatment. In our search for potent PapG‐II antagonists, we observed an increase in affinity when tetrasaccharide1, the natural ligand of PapG‐II in human kidneys, was elongated to hexasaccharide2, even though the additional Siaα(2–3)Gal extension is not in direct contact with the lectin. ITC studies suggest that the increased affinity results from partial desolvation of nonbinding regions of the hexasaccharide; this is ultimately responsible for perturbation of the outer hydration layers. Our results are in agreement with previous observations and suggest a general mechanism for modulating carbohydrate–protein interactions based on nonbinding regions of the ligand. Abstract : Water makes the difference : The affinity of galabiose (Galα(1–4)Gal)‐containing oligosaccharides for their target lectin PapG‐II is strongly influenced by desolvation of nonbinding parts of the oligosaccharide, and is ultimately associated with perturbation of the outer hydration layers. The proposed mechanism might play a more general role in carbohydrate–protein interactions.